Hematological features of pigs of different genotypes - Vashchenko, P.; Sukhno, V. (Scientific Progress & Innovations, 2022)
The reseaches of polymorphism of genes associated with natural resistance to diseases of breeding animals, and especially pigs, is becoming more and more relevant. The increased attention to this problem is explained by a number of factors, which include the widespread practice of using antibiotics in the industrial production of pig production during the last decades for prophylactic purposes and as growth stimulants, which caused the emergence of resistant strains of microorganisms to the most common antimicrobial drugs. In connection with the adopted legislative restrictions on the use of antibiotics in countries with developed animal husbandry, breeding and genetic methods of increasing the resistance of pigs have gained significant importance. At the same time, the predominant selection for one trait (in this case for resistance) can lead to unpredictable undesirable side effects, which should be detected before the introduction of such selection into industry practice. Hematological and biochemical indicators of blood are important markers of the general status of health, as well as the intensity of metabolism and a large number of other characteristics indirectly related to productivity. In order to prevent the appearance of undesirable consequences from selection, we set an aim to provide a comparative characterization of the hematological indicators of Ukrainian large white pigs (ULW-3) depending on their genotype according to DNA markers associated with resistance to infectious diseases of pigs. As a result of the research, it was established that AA (FUT 1) and TT (NRAMP1) genotypes are desirable for increasing resistance and have a positive effect on blood biochemical parameters (higher content of protein, albumins, higher activity of Aspartat- and Alanin-Aminotransferase enzymes), which is related to the fattening productivity of pigs (average daily gains, age of reaching live weight of 100 kg), however, a significant influence of genotype was established only for the NRAMP1 gene polymorphism. In the studied population of Large White Breed of intrabreed type ULW-3, no reliable influence of FUT 1 and NRAMP1 gene polymorphisms on the content of leukocytes, erythrocytes and hemoglobin was recorded, which makes it possible to carry out selection based on these genes without worsening hematological indicators.